2023
DOI: 10.1002/slct.202205000
|View full text |Cite
|
Sign up to set email alerts
|

Superior Adsorption Efficiency of MIL‐101 (Cr) and Nano‐MIL‐101 (Cr) in Anionic and Cationic Dye Removal from Aqueous Solution

Abstract: Metal‐organic frameworks (MOFs) as adsorbent have received considerable attention due to their remarkably high porosity, adjustable pore shape/size, and surface functionality. This study focusses on the adsorption performance and mechanism of two different typological and structural MOFs as superior adsorbents for the efficient removal of anionic and cationic dyes in an aqueous solution. MIL‐101(Cr) and nano‐MIL‐101(Cr) were successfully synthesized by the hydrothermal method using two different protocols and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
(163 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%